2021
DOI: 10.3389/fmicb.2021.727435
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of mcr-1-Carrying Plasmids From Gram-Negative Bacteria in a Dutch Tertiary Care Hospital: Evidence for Intrapatient and Interspecies Transmission Events

Abstract: The role of plasmids in the complex pandemic of antimicrobial resistance is increasingly being recognized. In this respect, multiple mobile colistin resistance (mcr) gene-carrying plasmids have been described. However, the characteristics and epidemiology of these plasmids within local healthcare settings are largely unknown. We retrospectively characterized the genetic composition and epidemiology of plasmids from mcr-1-positive bacterial isolates identified from patients from a large academic hospital in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Among such plasmids in our study, the IncX4 and IncI2 plasmid types were genetically similar, with the least variability, whereas the IncHI2/IncN plasmid type was divergent due to the fact that this type of double-Inc type plasmid contains multiple antimicrobial-resistant genes. This was consistent with the results of the two plasmids merging to perhaps increase the range of host species, plasmid fitness, and/or the acquisition of multiple antimicrobial-resistant genes 45 . Another study demonstrated that IncHI2-type plasmids are genetically divergent due to containing an MDR region which comprises a variable combination of antimicrobial-resistance genes and insertion sequences, such as Tn 6330 , in the IncHI2 type that is still highly active and is often transposable 37 .…”
Section: Discussionsupporting
confidence: 89%
“…Among such plasmids in our study, the IncX4 and IncI2 plasmid types were genetically similar, with the least variability, whereas the IncHI2/IncN plasmid type was divergent due to the fact that this type of double-Inc type plasmid contains multiple antimicrobial-resistant genes. This was consistent with the results of the two plasmids merging to perhaps increase the range of host species, plasmid fitness, and/or the acquisition of multiple antimicrobial-resistant genes 45 . Another study demonstrated that IncHI2-type plasmids are genetically divergent due to containing an MDR region which comprises a variable combination of antimicrobial-resistance genes and insertion sequences, such as Tn 6330 , in the IncHI2 type that is still highly active and is often transposable 37 .…”
Section: Discussionsupporting
confidence: 89%
“…This was also the case in the IncHI2 and IncX4plasmid sequenced in this study, which, respectively, presented either the truncated IS Apl1 - mcr-1 element or only the mcr-1 - pap2 genes with no trace of the original IS Apl1 sequences. Our results reinforce the hypothesis that the loss of the IS Apl1 sequences might favor the stabilization of the mcr-1 in a plasmidic backbone ( Strepis et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study 21 isolates from 14 patients were shown to be positive for mcr-1-containing plasmids, including IncX4, IncI2(delta), IncHI2, IncHI2/IncN, and IncHI2/IncQ. These plasmids were found in K. pneumoniae, Escherichia coli, and Kluyvera georgiana, and on the chromosome of K. pneumoniae ST147 [an ST of international high-risk] [61]. These Klebsiellaassociated plasmid transmission events carrying the broadest AMR gene repertoires amongst humans, animals, and the environment is an evolutionary process in need of urgent remedial action.…”
Section: One Health and The Relevance Of Klebsiella Speciesmentioning
confidence: 82%